Environmental determinants of fish community structure in gravel pit lakes. Issue 3 (23rd March 2015) - Zhao, Tian; Grenouillet, Gaël; Pool, Thomas; Tudesque, Loïc; Cucherousset, Julien
Abstract: Gravel pit lakes are increasingly common, and there is an urgent need to better understand the functioning of these artificial and disconnected ecosystems. However, our knowledge of the environmental determinants of fish community structure within these types of lakes remains poor. In this study, we quantified the taxonomic diversity, fish species and life‐stage composition in 17 gravel pit lakes sampled in 2012 and 2013 located in south‐west France to determine the potential role of environmental variables (i.e. lake morphology, productivity, water quality and human‐use intensity) as drivers of fish community structure and composition. Our results demonstrated that fish community structure significantly differed between gravel pit lakes, and we notably found that lakes managed for angling hosted higher levels of taxonomic diversity. We also found that young and large lakes supported higher native species biomass and were dominated by native European perch ( Perca fluviatilis ). Older, smaller and more productive lakes, located closer to the main urban area, supported a higher biomass of non‐native species such as largemouth bass ( Micropterus salmoides ). Native and non‐native sport fishing species such as northern pike ( Esox lucius ), pikeperch ( Sander lucioperca ), common carp ( Cyprinus carpio ) and cyprinid prey species were positively associated with fishery management effort, suggesting that management practices play also a critical role in shaping fish species composition. Overall, our study demonstrated that fish community composition followed a predictable shift along environmental gradients associated with the maturation of gravel pit lakes and the associated human practices.